Cystinosis-associated metabolic bone disease across ages and CKD stages 1 to 5D/T - Lahring, Johannes; Leifheit-Nestler, Maren; Ewert, Annika; Herzig, Nadine; Köppl, Christian; Pott, Veronika; Oh, Jun; Büscher, Anja; Thumfart, Julia; Weber, Lutz T; Arbeiter, Klaus; Acham-Roschitz, Birgit; et al. (The journal of clinical endocrinology & metabolism, 2025)
The pathophysiology of cystinosis-associated metabolic bone disease is complex.We hypothesized a disturbed interaction between osteoblasts and osteoclasts.This binational cross-sectional multicenter study included 103 patients with cystinosis (61% children) with chronic kidney disease (CKD) stages 1 to 5D/T at hospital clinics. Ten key bone markers were evaluated.Skeletal complications occurred in two-thirds of the patients, with adults having a 5-fold increased risk compared with children. Patients with CKD stages 1 to 3 showed reduced z-scores for serum phosphate and calcium and suppressed fibroblast growth factor 23 (FGF23) and parathyroid hormone levels, in conjunction with elevated bone-specific alkaline phosphatase levels. Serum phosphate was associated with estimated glomerular filtration rate, combined phosphate and active vitamin D treatment, and native vitamin D supplementation, while serum calcium was associated with age and dosage of active vitamin D. Sclerostin was generally elevated in children, and associated with age, FGF23 levels, and treatment with active vitamin D and growth hormone. The osteoclast marker tartrate-resistant acid phosphatase 5b was increased, and associated with age and treatment with active vitamin D. The ratio of soluble ligand of receptor activator of nuclear factor-κB (sRANKL) and osteoprotegerin (OPG), a surrogate for the regulation of osteoclastogenesis by osteoblasts, was decreased and associated with phosphate and 1,25(OH)2D3 levels. These changes were only partly corrected after transplantation.Bone health in cystinosis deteriorates with age, which is associated with increased osteoclast activity despite counter-regulation of osteoblasts via OPG/RANKL, which in conjunction with elevated sclerostin levels and persistent rickets/osteomalacia, may promote progressive bone loss.